Transcriptomic and Ultrastructural Analyses of Pyricularia Oryzae Treated With Fungicidal Peptaibol Analogs of Trichoderma Trichogin - Sella, Luca; Govind, Rakshita; Caracciolo, Rocco; Quarantin, Alessandra; Vu, Van V.; Tundo, Silvio; Nguyen, Hung Minh; Favaron, Francesco; Musetti, Rita; De Zotti, Marta (Frontiers in Microbiology, 2021)
Eco-friendly analogs of Trichogin GA IV, a short peptaibol produced by Trichoderma longibrachiatum, were assayed against Pyricularia oryzae, the causal agent of rice blast disease. In vitro and in vivo screenings allowed us to identify six peptides able to reduce by about 70% rice blast symptoms. One of the most active peptides was selected for further studies. Microscopy analyses highlighted that the treated fungal spores could not germinate and the fluorescein-labeled peptide localized on the spore cell wall and in the agglutinated cytoplasm. Transcriptomic analysis was carried out on P. oryzae mycelium 3 hours after the peptide treatment. We identified 1410 differentially expressed genes, two-thirds of which upregulated. Among these, we found genes involved in oxidative stress response, detoxification, autophagic cell death, cell wall biogenesis, degradation and remodeling, melanin and fatty acid biosynthesis, and ion efflux transporters. Molecular data suggest that the trichogin analogs cause cell wall and membrane damages and induce autophagic cell death. Ultrastructure observations on treated conidia and hyphae confirmed the molecular data. In conclusion, these selected peptides seem to be promising alternative molecules for developing effective bio-pesticides able to control rice blast disease.